(untitled) (Interdisciplinary Studies Journal, 2025)
Trisomy 21 is a genetic condition associated with alterations in cognitive and linguistic development. This study aimed to examine the effects of cognitive interventions aimed at stimulating working memory on the expressive vocabulary of a person with Trisomy 21. The experimental research, with a quantitative and qualitative approach, was conducted through structured activities with visual, auditory, and tactile stimuli. After the intervention, an increase in word production and a broadening of the lexical repertoire used in communicative contexts were observed. The design used allowed monitoring of the participant’s linguistic development, considering the interactions between working memory and lexical access. It was also noted that existing vocabulary tests have limitations that interfered with the analysis of the respondent’s true potential and development, as they present standards that are not flexible enough to address the sociocultural and regional characteristics of the potential subjects evaluated.